Comparative TVET Curriculum: Indonesia and Philippines Based on Indonesia's Vision 2045 - Hanif Aulia Kusuma; Lismi Animatul Chisbiyah; Wulidah Ning Tiasari; Ghasa Faraasyatul 'Alam; Ramadhana Setiyawan (IJECA (International Journal of Education and Curriculum Application), 2025)
Indonesia's Vision 2045 in the employment aspect, the first stage, is to anticipate job market disruption by facilitating access to reskilling and upskilling institutions in STEM areas of expertise. One of the reskilling and upskilling institutions in Indonesia is LKP. Based on this, this research aims to compare the LKP curriculum in Indonesia with the NCIII curriculum in the Philippines, which has been integrated with the STEM framework. The qualitative research approach of literacy study is applied in this study. The level of explanation in this study is a comparative study. To compare 2 curricula at different qualification levels, the AQRF framework is needed as an equalizer. Both curricula need to be converted according to the level in the AQRF, to produce an equivalent level. The results of comparing the two curricula show similarities and differences. In terms of similarities, both the LKP curriculum in Indonesia and the NCIII curriculum in the Philippines both adhere to the SILO approach to STEM, This approach indicates that each branch of science stands separately. Meanwhile, the difference is in the achievements of each element, for the LKP curriculum in Indonesia, competencies are separated based on work abilities, knowledge, attitudes, and values, whereas in the Philippines, the NCIII curriculum for each element of competency achievement is determined by the thinking skills domain, multiliteracies (is a soft skill in terms of literacy, for example, digital literacy, numeracy, and cultural literacy) in the STEM framework. NCIII is a national certification under the auspices of TESDA as the employment distribution authority in the Philippines. National certification is often used as a requirement for applying for jobs. Employment acceptance in Indonesia can accommodate employment acceptance in the Philippines, by using certification as a prerequisite for entering the workforce. The certification is proof that the candidate worker has adequate competence in the STEM field.